INTERACTION OF IMPULSE ELECTROMAGNETIC FIELDS WITH SURFACES OF METAL SAMPLES - V. V. Pavliouchenko; E. S. Doroshevich (Наука и техника)
Measurements of maximum tangential component of magnetic intensity Hτm have been carried out in the paper. The measurements have been taken on the surface of metal samples according to time of single current pulse rise in the form of semi-sinusoid of a linear current wire. Measurements have been made with the purpose to determine a value of the component according to thickness of samples made of aluminium.Temporary resolution ranges of electric and magnetic properties and defects of sample continuity along the depth have been found.Empirical formulae of dependence Hτm on sample thickness have been derived and their relation with efficient depth penetration of magnetic field into metal has been found.